2008
DOI: 10.1029/2007jd009695
|View full text |Cite
|
Sign up to set email alerts
|

High‐precision spectroscopy of 32S, 33S, and 34S sulfur dioxide: Ultraviolet absorption cross sections and isotope effects

Abstract: SO 2 and natural abundance samples were obtained from commercial manufacturers. The spectrum of the natural abundance sample is in agreement with previously published spectra. The spectra of the isotopically pure species were retrieved using the isotopic composition of the samples. The 32 SO 2 , 33 SO 2 , and 34 SO 2 absorption spectra show rich vibrational structure, and the positions and widths of the peaks change with isotopic substitution in a complex fashion. The results imply that large wavelength-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

27
142
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(173 citation statements)
references
References 53 publications
27
142
4
Order By: Relevance
“…These shifts were based on vibrational wavefunctions calculated using a single ab initio SO 2 excited potential energy surface (11,12). However, SO 2 has a score of electronic states in the relevant energy region with multiple curve crossings, giving rise to the complicated pattern seen in the experimental results (13). For example, three vibronic peaks of the three isotopologues are found between 200 and 205 nm (Fig.…”
Section: Effect Of Atmospheric Uv Shielding On Isotopic Fractionationmentioning
confidence: 99%
See 3 more Smart Citations
“…These shifts were based on vibrational wavefunctions calculated using a single ab initio SO 2 excited potential energy surface (11,12). However, SO 2 has a score of electronic states in the relevant energy region with multiple curve crossings, giving rise to the complicated pattern seen in the experimental results (13). For example, three vibronic peaks of the three isotopologues are found between 200 and 205 nm (Fig.…”
Section: Effect Of Atmospheric Uv Shielding On Isotopic Fractionationmentioning
confidence: 99%
“…Recent theoretical studies have examined the UV absorption spectra of SO 2 isotopologues (11) and have suggested that SO 2 self-shielding may have caused the Archean MIF record (12). However, the theoretical spectra necessarily contain several approximations and do not agree with recently obtained isotopologue-specific experimental spectra (13). The most straightforward way to determine the MIF effect is via direct measurement of UV absorption by SO 2 isotopologues.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…First, although the rate of SO 2 photolysis based on isotopologue-specific cross-sections in the region above the dissociation threshold at 220 nm do yield MIF fragments (18), the high concentration of O 2 in the modern atmosphere will rapidly reoxidize the SO to SO 2 , destroying any record of the process. Second, Pavlov et al (19) proposed that SO 3 photooxidation at wavelengths from 195 to 300 nm could explain sulfur MIF; however, in contrast to the highly structured SO 2 absorption spectrum, the absorption spectrum of SO 3 is smooth, reflecting direct photodissociation (20), and therefore, there is no physical reason why broadband solar photolysis of SO 3 would produce mass-independent enrichment.…”
mentioning
confidence: 99%